SIU-ICUD: Advances in Surgical Technique of Robotic Prostatectomy - Belén Mora-Garijo; Keith J. Kowalczyk (Société Internationale d’Urologie Journal)
Background/Objectives: Innovations in robotic prostatectomy have transformed a highly morbid operation to a procedure with fewer complications and shorter hospital stays, yet techniques continue to evolve. Our objective is to discuss the most recent advances in robotic prostatectomy techniques designed to minimize morbidity related to urinary incontinence and erectile dysfunction. Methods: This review is adapted from a comprehensive committee chapter on published in the 3rd WUOF/SIU (World Urologic Oncology Federation/Société Internationale d’Urologie) International Consultation on Urologic Diseases on Localized Prostate Cancer. Results: This review article describes both traditional and emerging techniques in robotic prostatectomy techniques and discusses their respective outcomes. Conclusions: Improved understanding of pelvic anatomy has enabled robotic-assisted techniques to preserve key structures and enhance recovery and functional outcomes while preserving oncologic safety